(untitled) (Journal of Science and Technology, 2016)
Libation, a common Ghanaian ritual, is fraught with numerous symbols, some of which the majority of Ghanaians are unaware of and therefore cannot appreciate as being Ghanaian. This verbal art is here presented from the perspective of the different ethnic contexts, in terms of the symbolisms, practices and interpretations that go with them, our understanding of which will foster a better awareness of one of the popular Ghanaian cultural practices which help to unify the people as a nation with identical cultural practices.